Frequency compensation schemes for operational amplifiers [electronic resource] - Tan, Chin Yee, 1982- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2010